The role of Muslim women in civil society in promoting values and principles for building peace: action guide from the Qur’ān = Peranan wanita Muslim dalam masyarakat awam dalam mempromosikan nilai dan prinsip untuk membina keamanan: panduan tindakan dari Al-Quran - Bahari, Che Amnah; Abdullah, Fatimah (Centre for Core Studies, Universiti Sains Islam Malaysia (USIM), 2019)
The Muslim World in particular has witnessed conflicts in different areas, which have hindered the developmental efforts of the nations concerned. Most victims of these conflicts are women and children. This article attempts to elaborate the role of Muslim women as a crucial segment in civil society in initiating peace building through the nurturing process. It maintains that the adoption of the principles and values derived from the Qur’ān and Sunnah of the Prophet is necessary as a process of lifelong learning. Those identified values constitute the framework of this article, and it adopts the method of textual analysis. This article concludes that through the implementation of Islamic values and frameworks for peace building, Muslim women in a civil society are able to play a significant role in initiating peace building and promoting peaceful coexistence in a pluralistic society.